Receptive Field Positions in Area MT during Slow Eye Movements - Hartmann, Till S. (Society for Neuroscience, 2011)
Perceptual stability requires the integration of information across eye movements. We first tested the hypothesis that motion signals are integrated by neurons whose receptive fields (RFs) do not move with the eye but stay fixed in the world. Specifically, we measured the RF properties of neurons in the middle temporal area (MT) of macaques (Macaca mulatta) during the slow phase of optokinetic nystagmus. Using a novel method to estimate RF locations for both spikes and local field potentials, we found that the location on the retina that changed spike rates or local field potentials did not change with eye position; RFs moved with the eye. Second, we tested the hypothesis that neurons link information across eye positions by remapping the retinal location of their RFs to future locations. To test this, we compared RF locations during leftward and rightward slow phases of optokinetic nystagmus. We found no evidence for remapping during slow eye movements; the RF location was not affected by eye-movement direction. Together, our results show that RFs of MT neurons and the aggregate activity reflected in local field potentials are yoked to the eye during slow eye movements. This implies that individual MT neurons do not integrate sensory information from a single position in the world across eye movements. Future research will have to determine whether such integration, and the construction of perceptual stability, takes place in the form of a distributed population code in eye-centered visual cortex or is deferred to downstream areas.